Comparison of obesity based on various obesity indices in metabolic dysfunction-associated fatty liver disease (MAFLD) subjects: A comparative analysis of anthropometric and bioimpedance indices - Hamid, Widya Inarah Nadhilah; Aman, Andi Makbul; Rasyid, Haerani; Bakri, Syakib; Daud, Nu'man As; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a terminology that describes the condition of fatty liver accompanied by metabolic disorders. Previous studies have shown obesity is associated with MAFLD, but fatty liver can also be observed in non-obese individuals. The obesity measurement index can reflect obesity levels and can be used as a screening tool for metabolic diseases such as MAFLD. In addition to Body Mass Index (BMI), there are several other measurement indices, such as Waist Circumference (WC), Waist-to-Height Ratio (WHtR), as well as Body Fat Percentage (BF%) and Fat Mass Index (FMI). This study aims to see the comparison of obesity prevalence in MAFLD patients based on various measurement indices.Methods: This study was conducted at Wahidin Sudirohusodo Hospital in Makassar, Indonesia, using an observational study with a cross-sectional design. The various obesity indices were performed once the patient was newly diagnosed with MAFLD. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25.0.Results: This study consisted of 44 males (57.9%) and 32 females (42.1%), with an average age 41.8 years. The prevalence of obesity based on various indices in MAFLD subjects was as follows: WHtR (100%), LP (88.2%), FMI (86.8%), BF% (86.8%), and BMI (80.3%).Conclusions: The prevalence of obesity in MAFLD subjects was highest when measured by the WHtR index, followed by WC, FMI, BF%, and lowest when measured by BMI.